2023
DOI: 10.3390/ani13071257
|View full text |Cite
|
Sign up to set email alerts
|

Ruminating, Eating, and Locomotion Behavior Registered by Innovative Technologies around Calving in Dairy Cows

Abstract: The hypothesis for this study was that there are correlations between ruminating, eating, and locomotion behavior parameters registered by the RumiWatch sensors (RWS) before and after calving. The aim was to identify correlations between registered indicators, namely, rumination, eating, and locomotion behavior around the calving period. Some 54 multiparous cows were chosen from the entire herd without previous calving or other health problems. The RWS system recorded a variety of parameters such as rumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Additionally, this study observed a gradual return to pre-calving activity levels within two weeks postpartum, indicating successful adaptation [ 11 ]. Interestingly, the present study’s findings slightly differ from the findings of [ 56 ], which indicated a quicker normalization of activity levels occurring nine days after calving, showing a recuperation from calving stress. Furthermore, these collective findings emphasize the importance of understanding and managing postpartum behavior to maximize cow comfort and welfare.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, this study observed a gradual return to pre-calving activity levels within two weeks postpartum, indicating successful adaptation [ 11 ]. Interestingly, the present study’s findings slightly differ from the findings of [ 56 ], which indicated a quicker normalization of activity levels occurring nine days after calving, showing a recuperation from calving stress. Furthermore, these collective findings emphasize the importance of understanding and managing postpartum behavior to maximize cow comfort and welfare.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, several papers recently appeared in the literature related to our works. Studies on feeding behaviors around calving in dairy cattle [22] and predicting the feed intake of cattle based on jaw movement using a triaxial accelerometer [23] are some of them. Although the approaches are different from ours, since feeding time estimation and feed intakes are related, further analysis would be worthwhile to investigate in more detail [24,25].…”
Section: Discussionmentioning
confidence: 99%